Identification of Hearing Loss-Associated Variants of PTPRQ, MYO15A, and SERPINB6 in Pakistani Families. (28th April 2021) - Mahmood, Umair; Bukhari, Shazia A.; Ali, Muhammad; Ahmed, Zubair M.; Riazuddin, Saima
Abstract : The inner ear is an essential part of a well-developed and well-coordinated hearing system. However, hearing loss can make communication and interaction more difficult. Inherited hearing loss (HL) can occur from pathogenic genetic variants that negatively alter the intricate inner ear sensory mechanism. Recessively inherited forms of HL are highly heterogeneous and account for a majority of prelingual deafness. The current study is designed to investigate genetic causes of HL in three consanguineous Pakistani families. After IRB approval, the clinical history and pure tone audiometric data was obtained for the clinical diagnosis of HL segregating in these three Pakistani families. We performed whole exome sequencing (WES) followed by Sanger sequencing in order to identify and validate the HL-associated pathogenic variants, respectively. The 3-D molecular modeling and the Ramachandran analysis of the identified missense variants were compiled to evaluate the impact of the variants on the encoded proteins. Clinical evaluation revealed prelingual severe to profound sensorineural HL segregating among the affected individuals in all three families. Genetic analysis revealed segregation of several novel variants associated with HL, including a canonical splice-site variant (c.55-2A>G) of PTPRQ in family GCFHL-01, a missense variant [c.1079G>A; p.(Arg360Gln)] of SERPINB6 in family LUHL-01, and an insertion variant (c.10208-10211insCCACCAGGCCCGTGCCTC) within MYO15A in family LUHL-011. All the identified variants had very low frequencies in the control databases. The molecular modeling of p.Arg360Gln missense variant also predicted impaired folding of SERPINB6 protein. This study reports the identification of novel disease-causing variants in three known deafness genes and further highlights the genetic heterogeneity of HL in Pakistani population.